Adaptability and Performance of Slag Cement As Partial Replacement to Ordinary Portland Cement in Concrete - Manaloto, John Arvin R. (MUHON: A Journal of Architecture, Landscape Architecture, and the Designed Environment; Issue Number 8, 2022)
Portland cement is extensively used in the construction industry, making it one of the biggest construction expenditures in the Philippines and worldwide. It plays a vital role in concrete technology and is also the one used more often as compared to the other types of cement. In this study, the feasibility of partially replacing Portland cement with Slag cement, an industrial byproduct of iron manufacturing was investigated. This provides alternative and sustainable solutions to concrete design that could aid in the construction cost reduction. In this research, the effect of replacing Portland cement with 0 percent, 30 percent, 40 percent and 50 percent slag cement in concrete mix design were investigated for compressive and flexural strengths. For the determination of strengths, a Universal Testing Machine (UTM) was used to apply compressive and flexural loads to concrete cylindrical and beam samples, respectively. Water demand, slump and slump retention at constant water-cement ratio for the said proportions were also tested. The results show that concrete using slag cement has lower water demand as it achieves higher slump and better slump retention versus concrete using pure Portland cement. Moreover, with the increasing amount of slag cement replacement to Portland cement, the compressive and flexural strength of concrete increases. An optimum replacement of 50 percent slag cement to Portland cement in concrete is therefore recommended for both compressive strength and flexural strength designs. Keywords: concrete mix design, Portland cement replacement, slag cement